2016
DOI: 10.4049/jimmunol.1501574
|View full text |Cite
|
Sign up to set email alerts
|

Long-Peptide Cross-Presentation by Human Dendritic Cells Occurs in Vacuoles by Peptide Exchange on Nascent MHC Class I Molecules

Abstract: Cross-presentation enables dendritic cells to present on their MHC class I molecules antigenic peptides derived from exogenous material, through a mechanism that remains partly unclear. It is particularly efficient with long peptides, which are used in cancer vaccines. We studied the mechanism of long-peptide cross-presentation using human dendritic cells and specific CTL clones against melanoma Ags gp100 and Melan-A/MART1. We found that cross-presentation of those long peptides does not depend on the proteaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…In this pathway the presentation of exogenous antigens does not require proteasomes or TAP (33, 83, 84, 85). Instead, the presented peptides are generated by protein catabolism within the endocytic compartments and then loaded on MHC I molecules in these vesicles (33, 8688) (Figure 3, Step 2).…”
Section: Pathways Of Xpt Of Antigens In Phagosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this pathway the presentation of exogenous antigens does not require proteasomes or TAP (33, 83, 84, 85). Instead, the presented peptides are generated by protein catabolism within the endocytic compartments and then loaded on MHC I molecules in these vesicles (33, 8688) (Figure 3, Step 2).…”
Section: Pathways Of Xpt Of Antigens In Phagosomesmentioning
confidence: 99%
“…This may be particularly important for the P2C pathway because in many systems P2C XPT is inhibited by BFA, indicating that the export of some newly synthesized proteins, most likely MHC I molecules, out of the ER/golgi is needed for this pathway (76, 77). Direct transport of MHC I from the ER to endocytic compartments may also be important to vacuolar XTP because, in at least one system, it required newly synthesized MHC I molecules and was not blocked by an inhibitor of endosomal recycling, primaquine (83). …”
Section: Phagosomal Mhc I Trafficking and Peptide Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental protocol is shown in Figure . Two antigens, the long (26 aa) MelanA peptide, which requires processing to be presented on HLA‐A2, and the short (10aa) 26–35 epitopic peptide, which directly binds the HLA‐A2 groove, were compared at equimolar concentrations for their ability to stimulate the LT12 MelanA‐specific HLA A2‐restricted CTL clone. Monocytes were pulsed for 3 hr, extensively washed before co‐culture with T lymphocytes either immediately (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-presentation has been shown to be facilitated by a TAP-dependent cytosolic pathway of phagocytosis, 71 and also by TAP independent pathways. 72 Recently, Ma et al 73 demonstrated a novel vacuolar pathway of cross-presentation, in which long peptides derived from melanoma tumor associated antigens (TAAs) are cross presented by DCs to CD8 + T cells in a proteasome and TAP-independent fashion. The direct contribution of cross-presentation to immunodominance has been best demonstrated in the context of influenza.…”
Section: Further Complications: the Unpredictability Of Cross-presentmentioning
confidence: 99%